Development and Characterization of Orodispersible Tablets Containing Sumatriptan Succinate and Feverfew for the Treatment of Migraine - Swati Modgekar; Vijayanand Pujari; Rashmi Surve; Rahul Koli (RGUHS Journal of Pharmaceutical Sciences)
Background Migraine a chronic neurological disorder is characterized by moderate to severe headache episodes. Sumatriptan succinate an FDA-approved treatment for migraine in adults has demonstrated efficacy. Meanwhile Feverfew with a traditional application for fever and migraine provides herbal avenue for therapeutic intervention. This study seeks for the synergistic effect of both drugs by formulating orodispersible tablets ODT with a blend of synthetic and herbal drugs employing superdisintegrants and the sublimation technique.Methods The ODTs were crafted via direct compression method using superdisintegrants croscarmellose sodium crospovidone and sodium starch glycolate at varying concentrations 2 4 and 6. Kyron T114 was employed to mask the bitter taste of Sumatriptan succinate. The optimized formulation selected based on the least disintegration time DT underwent reformulation using sublimating agents camphor thymol or menthol at varying concentrations 1 2 3 to further minimize DT.Results Evaluation of pre- and post-compression parameters including weight variation hardness friability DT and in-vitro drug release met specified limits. The formulation featuring 6 crospovidone and 2 menthol exhibited a DT of 14 seconds and achieved drug release gt90 within five minutes thus was identified as the optimized formulation. Accelerated stability studies and kinetic modelling were conducted for this formulation.Conclusion The synergistic combination of synthetic and herbal components in the optimized ODT offers a novel therapeutic approach for migraine management emphasizing both patient compliance and treatment effectiveness.